In vitro Propagation of Stemona tuberosa Lour. - A Rare Medicinal Plant through High Frequency Shoot Multiplication using Nodal Explants (Plant Tissue Culture and Biotechnology, 2011)
Nodal segments of Stemona tuberosa Lour. were found to proliferated without any differentiation on to MS supplemented with 3.0 mg/l BAP and 0.5 mg/l NAA under continuous dark condition. After 20 days of inoculation under dark condition the cultures were transferred to a daily cycle of 16/8 hrs light/dark photoperiod and there the proliferated nodal segments underwent direct organogenesis producing huge number of shoot buds (25.87/culture). The shoot buds underwent rapid elongation on a range of BAP (0.1 - 1.5 mg/l) and IBA (0.1 - 1.0 mg/l) supplemented MS. Rooting of elongated shoot buds was successfully achieved (90%) in half strength MS with 1.0 mg/l NAA. The plantlets were finally established in outside environment through a successive phase of acclima-tization.   Key words: Nodal explant, Stemona tuberose, Rare medicinal plant, Direct organogenesis   D. O. I. 10.3329/ptcb.v21i2.10238   Plant Tissue Cult. & Biotech. 21(2): 151-159, 2011 (December)